Transcriptional Profiling and Genetic Mapping of Barley Responses to Bacterial Flagellin - Elizabeth K. Brauer; Whynn Bosnich; Monique Power; Doris Luckert; Sarita Khanal; Nathan Liang; Reid James; Moatter Syed; Martin Charette; Danielle Wolfe; Arezo Pattang; Hannah Morrison; et al. (Molecular Plant-Microbe Interactions)
Diverse plant species detect bacterial flagellin using leucine-rich repeat receptor-like kinases to activate defense responses and promote resistance against bacterial invasion. In barley, the impact of flagellin on inducible defense responses has not been fully described. Here, we report that the flagellin-derived flg22 peptide induces callose, reactive oxygen species (ROS) bursts, and differential expression of 2,603 genes in barley. Cultivated barley genotypes produce different amplitudes of flg22-induced ROS bursts, indicating genetic variation for microbe-associated molecular pattern responses. Association mapping revealed a region on chromosome 7 underlying variation in flg22-induced ROS bursts, which contains 12 flg22-induced genes. Genotypes with higher flg22 responses had higher induced resistance to Xanthomonas translucens pv. translucens (Xtt), the causal organism of bacterial leaf streak. The flg22 region of Xtt flagellin evades detection in both barley and Arabidopsis, and a single amino acid change can restore immunogenicity of the peptide. Together, this work underlines the effectiveness of the flagellin-triggered defenses in promoting barley resistance to Xtt, which evades recognition of the flg22 region in its host. [Figure: see text]Copyright © 2025 His Majesty the King in Right of Canada, as represented by the Minister of Agriculture and Agri-Food Canada. This is an open access article distributed under the CC BY-NC-ND 4.0 International license.